Genome‐wide screening reveals that miR‐195 targets the TNF‐α/NF‐κB pathway by down‐regulating IκB kinase alpha and TAB3 in hepatocellular carcinoma. Issue 2 (26th June 2013) - Ding, Jie; Huang, Shenglin; Wang, Ying; Tian, Qi; Zha, Ruopeng; Shi, Haibing; Wang, Qifeng; Ge, Chao; Chen, Taoyang; Zhao, Yingjun; Liang, Linhui; Li, Jinjun; et al.
<x xml:space="preserve">Abstract</x> Nuclear factor kappa B (NF‐κB) is an important factor linking inflammation and tumorigenesis. In this study we experimentally demonstrated through a high‐throughput luciferase reporter screen that NF‐κB signaling can be directly targeted by nearly 29 microRNAs (miRNAs). Many of these miRNAs can directly target NF‐κB signaling nodes by binding to their 3′ untranslated region (UTR). miR‐195, a member of the miR‐15 family, is frequently down‐regulated in gastrointestinal cancers, especially in hepatocellular carcinoma (HCC). The expression level of miR‐195 is inversely correlated with HCC tumor size. We further show that miR‐195 suppresses cancer cell proliferation and migration in vitro and reduces tumorigenicity and metastasis in vivo. Additionally, miR‐195 may exert its tumor suppressive function by decreasing the expression of multiple NF‐κB downstream effectors by way of the direct targeting of IKKα and TAB3. Conclusion: Multiple miRNAs are involved in the NF‐κB signaling pathway and miR‐195 plays important inhibitory roles in cancer progression and may be a potential therapeutic target. (Hepatology 2013;58:654–666)